Growing in Tandem with Media: Fantasy Sport, Media Use, and the Formation of an Industry Giant. Issue 1 (14th July 2021) - Billings, Andrew C.; Buzzelli, Nicholas R.; Fan, Minghui
Abstract: The growth in sports media, both in the number and quality of content options, is surpassed only by the escalation of fantasy sport participants, moving from niche to mainstream over a relatively short time. This essay tracks the paths of both sport media and fantasy industry growth, arguing that the symbiotic relationship between the two has facilitated growth that could not have been accomplished without the presence of both.